Pengaruh Motivasi Berwirausaha, Kecerdasan Emosional Dan Literasi Digital Terhadap Keberhasilan Usaha SWK Taman Prestasi Surabaya - Tri Indah Sari; Awin Mulyati; Ute Chairuz M. Nasution (Jurnal Dinamika Administrasi Bisnis, 2026)
The purpose of this study is to examine how business actors in the Taman Prestasi Culinary Tourism Center (SWK) Surabaya are influenced by Entrepreneurial Motivation, Emotional Intelligence, and Digital Literacy. The importance of internal factors of business actors in increasing business success amidst tight competition and rapid advances in digital technology is the main driver of this study. Entrepreneurial Motivation, Emotional Intelligence, and Digital Literacy are seen as factors that can encourage business growth and sustainability. This study uses a quantitative method with a causal associative approach. The study population consists of 35 business actors in the Taman Prestasi Culinary Tourism Center (SWK) Surabaya. To use the complete population as a research sample, the sampling strategy uses a saturated sample method, where the entire population is sampled. Data collected through questionnaire distribution and analyzed using SPSS version 25.0, used to evaluate the data using validity, reliability, classical assumptions, multiple linear regression analysis, and the coefficient of determination (R²). The findings indicate that entrepreneurial motivation, emotional intelligence, and digital literacy positively and significantly influence the business success of entrepreneurs at Taman Prestasi Surabaya's SWK business. The coefficient of determination (R²) of 0.718 indicates that entrepreneurial motivation, emotional intelligence, and digital literacy account for 71.8% of the business success, while other factors outside the study contribute to the remaining 28.2%. Therefore, increasing entrepreneurial motivation, emotional intelligence, and digital literacy can contribute to the business success of entrepreneurs at Taman Prestasi Surabaya's SWK business.